Magnetic Resonance and Coronarographic Study of Rat Heart During Artificial Hypobiosis - Umanska, Anna O.; Melnychuk, Dmytro O.; Melnychuk, Sergey D.; Kalachniuk, Liliya H. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 181.